The evolution of the financial technology ecosystem : an introduction and agenda for future research on disruptive innovations in ecosystems - Palmié, Maximilian; Wincent, Joakim; Parida, Vinit; Caglar, Umur (Elsevier, 2020)
At a time when many mature industries have been fundamentally transformed by disruptive innovations, prominent examples such as Apple and Uber reflect how disruptive innovations often originate at the ecosystem or system level rather than in individual firms. Unfortunately, the academic literature has paid little attention to the role of ecosystem development and evolution in relation to disruptive innovations. To overcome this oversight, our study defines disruptive innovation ecosystems and illustrates the impact that the financial technology (FinTech) ecosystem has had on disrupting the financial services industry. We offer an agenda for future research on disruptive innovations and ecosystems and discuss the evolution of the FinTech ecosystem. Our study shows that disruptive innovation ecosystems are not only in need of but also deserving of further attention.
Keywords: disruptive innovation; digitalization; ecosystems; financial technology; FinTech; artificial intelligence; entrepreneurship; incumbents; fi=Johtaminen ja organisaatiot|en=Management and Organization|